ANALYSIS OF TOURISM CONTENT FRAMING ON TRAVELOKA YOUTUBE - Novi Anggraini; Abdul Rasyid (Program Pascasarjana UIN Sumatera Utara, 2026)
The development of digital media has positioned YouTube as a strategic platform for shaping tourism perceptions through audiovisual content. This study aims to analyze the framing of tourism content on Traveloka’s YouTube channel using Robert N. Entman’s framing model. Employing a descriptive qualitative method, this research examines the video “Itinerary and Budget Trip Sumba 5D4N.” The findings indicate that Traveloka frames Sumba as an exotic and challenging destination that remains accessible through well-planned travel supported by integrated digital services. The use of a daily vlog format with personal storytelling receives positive responses from audiences, as it fosters emotional engagement and presents an authentic travel experience. However, this study also identifies limitations in the content, particularly the lack of explicit information regarding worship facilities and the halal or non-halal status of food, which are essential for Indonesian travelers. These findings suggest that while Traveloka’s framing is strong in visual and emotional aspects, there is room for improvement to create more comprehensive and audience-responsive tourism content.